IMPLEMENTATION OF SAFETY REQUIREMENTS IN THE CONSTRUCTION INDUSTRY IN LIBYA - Mohamed Salem Masoud Zekri; Kusdi Rahardjo; Arik Darmawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Construction industry is both economically and socially important. The prevention of construction accidents usually entails predicting future accidents and their nature under given circumstances. Due to the fact that accident rates in construction are high when compared to other industries, the construction and projects managers need to be fully prepared to deal with accidents when they occur, undertaking proper investigations and reporting procedures afterwards.